DISTURBANCES IN HEMOSTASIS AND PHYSICOCHEMICAL PROPERTIES OF THE BLOOD - Гришко, Ю.М. (World of Medicine and Biology, 2016)
Hemostasis is a problem that has always been of high interest as this is not only one of the protection systems that ensure homeostasis, normal functioning of the body, and because in general pathological patterns of damage intravascular platelet aggregation and blood coagulation play an important role, are a component of the pathogenesis of diverse etiology and clinical manifestations of disease, exercise influence over, the recovery may be the immediate cause of death of the patient. Knowledge of the pathogenesis of hemostatic disorders, DIC clinic and complications caused by them, the ability to take into account the importance of these disorders in disease specific patient allow to carry out targeted pathogenetic therapy that can significantly increase the effectiveness of treatment.
Keywords: hemostasis; blood coagulation; platelets